Omicron: Egyptian nurses' knowledge and attitudes - Mostafa Shaban; Marwa Mamdouh Shaban; Osama Ramadan; Huda Hamdy Mohammed (Wolters Kluwer Medknow Publications, 2022)
Objective: The current study aimed to assess the knowledge and attitudes of nurses toward the current COVID-19 pandemic and Omicron variant. Materials and Methods: A cross-sectional online survey was used. Totally 277 Egyptian nurses completed an electronic questionnaire comprising demographics with 5 items, nurses' knowledge on Omicron with 18 questions, and nurses' attitudes on Omicron with 5 questions. The data collected were expressed using numbers, percentages, and mean and standard deviation. Results: The mean age of nurses was 27 ± 5 years, nearly 50% of the nurses were bachelor degrees. The total score of correct answers related to knowledge was 75%, showing the different degrees of knowledge about Omicron. The majority of nurses showed positive attitudes toward controlling and managing the COVID-19 pandemic. Conclusions: Egyptian nurses have average knowledge about Omicron and a positive attitude toward controlling the COVID-19 pandemic. There should be scope for further assessment to enhance understanding about COVID-19. Moreover, health education programs should be developed for nursing staff to improve information, beliefs, behaviors, and attitudes towards the Omicron variant in particular and the COVID-19 pandemic in general.